Usefulness of self-assessment checklist in neurophysiological laboratory hands-on training - Okabe, Isao; Enoki, Kazunori; Taniguchi, Mina; Demura, Ai; Kinoshita, Masako (Japanese Journal of Clinical Neurophysiology, 2019)
We investigated the usefulness of self-assessment checklist on knowledge and degree of proficiency in neurophysiological laboratory hands-on training of medical technologists. Eleven medical technologists, 2.2±1.9 (mean±SD) years of experience, who participated in the EEG hands-on training courses for three days were evaluated. In basic course 68 check items were set, and in advanced course 30 additional items (98 in total) were set. Each item was self-evaluated in three levels (A: fully skilled and able to implement/judge by oneself, B: fully learned but unconfident about implementing/judging by oneself, C: Not fully learned) before and after the hands-on training. Trainees also evaluated the satisfaction level of the training. Ratio of level A increased from 5.5±8.6% to 47.9±23.8% after the training. The degree of satisfaction of the training was 4.6±0.5 out of 5. By using checklists for neurophysiological hands-on training, trainees can confirm their knowledge and degree of mastery, and trainers can plan throughly. Training course for only three days is insufficient to be able to implement/judge the whole items by oneself.